Some Aspects of Diamonds in Scientific Research and High Technology - Lipatov, Evgeniy (IntechOpen, 2020)
This book considers some aspects of diamond-based technologies: CVD diamond synthesis, application of diamond as a material with high hardness and thermal conductivity, and the investigation of charge carrier transport properties of synthetic diamond and chemical properties of diamond surfaces.